Sexual and reproductive health of adolescent Syrian refugee girls in Lebanon: a qualitative study of healthcare provider and educator perspectives - Sasha Abdallah Fahme; Maia Sieverding; Sawsan Abdulrahim (BMC, 2021)
Plain language summary Studies suggest that adolescent Syrian refugee girls in Lebanon are at risk of early marriage and related poor sexual and reproductive health outcomes, yet little is known about this population's specific sexual and reproductive health needs and care-seeking practices. To help fill this gap, we conducted a qualitative study with healthcare providers and educators who provide adolescent Syrian refugee girls with sexual and reproductive health services and education. The study aimed to better understand this population's health needs and behaviors to aid in the development of a sexual and reproductive health program for Syrian refugee girls that seeks to reduce early marriage. Respondents identified adolescent pregnancy, reproductive tract infections and sexual and gender-based violence as major health issues in this population. Early marriage, disruption of education, restrictive gender roles and men's detachment from healthcare were all recognized as potential risk factors. Stigma and bias, even among the study participants themselves, were also found to be potential barriers to care. We adapted a behavioral model for healthcare-seeking practices among vulnerable populations to categorize these risks and develop recommendations for health interventions in this community. Sexual and reproductive health initiatives in this population should be multi-faceted, community-based and aimed not only at adolescents but also their spouses and parents, who hold decision-making power.